3D fluid–structure interaction simulation of an hydrofoil at low Reynolds number. (May 2022) - Salmon, Fabien; Chatellier, Ludovic
Abstract: Understanding the interaction between wings and fluids is of great interest in many fields such as aeronautics, wind turbines, civil engineering, naval and industrial domain, among others. To improve our knowledge, scientists have conducted more and more theoretical studies with numerical simulation. Due to the high complexity of the coupled phenomena leading to time-consuming fluid–structure interaction simulations, the overwhelming majority of these studies are restricted to two dimensions. Here, we present the full three-dimensional fluid–structure simulation of a foil in water. A deformable NACA 0015 wing, at 15° angle of attack, undergoes a 1 m . s − 1 flow in a water tunnel. We handle the simulation with free open-source software: OpenFOAM (fluid), CalculiX (solid) and preCICE (fluid–structure coupling). An implicit coupling is considered. The access to high-performance computing facilities allows us to run a Delayed-Detached-Eddy Simulation (DDES) based on a 15-million-cell mesh resolving the boundary layer on the wing. We also develop a meshing tool based on free software and Python scripts to facilitate the meshing process of wings or any shape in rectilinear geometries (2D and 3D). Then, we manage a thorough numerical investigation of the 3D phenomena involved in this fluid–structure problem. In particular, we reproduce the vortex-induced vibration process and observe the same fundamental frequency for the vortex shedding, the wing displacement oscillation and the lift and drag coefficients. Thus, we evidence that wing oscillatory displacements, of the order of 0.1% of the chord only, significantly affect the behavior of the flow.